Reproductive, obstetric, and perinatal outcomes of women with adenomyosis and endometriosis: a systematic review and meta-analysis. (18th July 2019) - Horton, Joanne; Sterrenburg, Monique; Lane, Simon; Maheshwari, Abha; Li, Tin Chiu; Cheong, Ying
Abstract: BACKGROUND: The reproductive impact of adenomyosis and endometriosis is widely researched but the extent of these impacts remains elusive. It has been demonstrated that endometriosis, in particular, is known to result in subfertility but endometriosis and adenomyosis are increasingly linked to late pregnancy complications such as those caused by placental insufficiency. At the molecular level, the presence of ectopic endometrium perturbs the endometrial hormonal, cellular, and immunological milieu, negatively influencing decidualization, placentation, and developmental programming of the embryo. It is unclear if and how such early aberrant reproductive development relates to pregnancy outcomes in endometriosis and adenomyosis. OBJECTIVE AND RATIONALE: The aims of this systematic review and meta-analysis were to (i) investigate the association of adenomyosis and endometriosis with fertility, obstetric, and neonatal outcomes of women through both assisted reproduction and natural conception and (ii) determine whether endometriosis disease subtypes have specific impacts on different stages of the reproductive process. SEARCH METHODS: A systematic literature review of NHS evidence electronic databases and the Cochrane database identified all comparative and observational studies between 1980 and December 2018 in any language on adenomyosis and endometriosis with fertility, obstetric, and neonatal outcomes (23 search terms used). A total of 104 papers were selected for data extraction and meta-analysis, with use of Downs and Black standardized checklist to evaluate quality and bias. OUTCOMES: We found that endometriosis consistently leads to reduced oocyte yield and a reduced fertilization rate (FR), in line with current evidence. Milder forms of endometriosis were most likely to affect the fertilization (FR OR 0.77, CI 0.63–0.93) and earlier implantation processes (implantation rate OR 0.76, CI 0.62–0.93). The more severe disease by American Society for Reproductive Medicine staging (ASRM III and IV) influenced all stages of reproduction. Ovarian endometriosis negatively affects the oocyte yield (MD −1.22, CI −1.96, −0.49) and number of mature oocytes (MD −2.24, CI −3.4, −1.09). We found an increased risk of miscarriage in both adenomyosis and endometriosis (OR 3.40, CI 1.41–8.65 and OR 1.30, CI 1.25–1.35, respectively), and endometriosis can be associated with a range of obstetric and fetal complications including preterm delivery (OR 1.38, CI 1.01–1.89), caesarean section delivery (OR 1.98 CI 1.64–2.38), and neonatal unit admission following delivery (OR 1.29, CI 1.07–1.55). WIDER IMPLICATIONS: Adenomyosis and the subtypes of endometriosis may have specific complication profiles though further evidence is needed to be able to draw conclusions. Several known pregnancy complications are likely to be associated with these conditions. The complications are possibly caused by dysfunctional uterine changes leading to implantation and placentation issues and therefore could potentially have far-reaching consequences as suggested by Barker's hypothesis. Our findings would suggest that women with these conditions should ideally receive pre-natal counselling and should be considered higher risk in pregnancy and at delivery, until evidence to the contrary is available. In order to expand our knowledge of these conditions and better advise on future management of these patients in reproductive and maternal medicine, a more unified approach to studying fertility and reproductive outcomes with longer term follow-up of the offspring and attention to the subtype of disease is necessary.